Avaliação in vitro da precisão de modelos obtidos a partir de três técnicas de moldagem de transferência de implantes, utilizando um silicone de adição, um silicone de condensação, um poliéter e um alginato - Modesto, Luiz Cláudio Pepino (2010)
The passive adaptation of implant-prosthesis is of paramount importance for the maintenance of normal complex prosthesis, implant, bone and periodontal tissues. The absence of this passivity generates stress between the fit of components, which propagates along the implant and this tension is expressed without loss of osseintegration fracture of the screw, the implant and the biological order issues, the retention of the biofilm. This study aimed to compare four impression materials, a silicone additive, a condensation silicone, a polyether and alginate molding techniques and three with open tray with square transferor splints, not splint do with closed tray. From a human jaw model with four conical abutment analogs, using the four techniques of molding and transfer molding of four subjects. The molds were poured with special plaster, and the models were compared by means of optical microscopy led to the microscope, where he made the measurements of misfit between the bar and analogues. It was concluded that for the open tray technique provides the best results in relation to the techniques employed in the study, compared the four types of materials in the open tray technique WITHOUT splinting groups reached statistical significance ADSIL IMPREGNUM x, x ADSIL ALGINATE, SPEEDEX and x IMPREGNUM SPEEDEX and alginate, the open tray technique WITH splinting materials compared in groups reached statistical significance only groups SPEEDEX IMPREGNUM x and x SPEEDEX ALGINATE, and closed tray technique in only one group and reached statistical significance ADSIL SPEEDEX level alpha <0.05.